2021
DOI: 10.1002/slct.202101719
|View full text |Cite
|
Sign up to set email alerts
|

Applications of 3,5‐Dialkyl‐4‐nitroisoxazoles and Their Derivatives in Organic Synthesis#

Abstract: Dedicated to Prof. A. Ramachandraiah on his superannuation from the servicesThe methyl/methylene group present at the 5 th position of 3,5dialkyl-4-nitroisoxazoles show characteristic reactivity because of the presence of À NO 2 at the 4 th position in the structure. This methyl/methylene is used for the generation of carbanion that undergo Knoevenagel condensation, vinylogous nitroaldol (Henry type), Mannich and Michael addition reactions. The unsaturated systems generated by Knoevenagel condensation are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 188 publications
0
3
0
Order By: Relevance
“…Adamo and co-workers developed 3-methyl-4-nitro-5-alkenyl-isoxazole 1 , bearing a γ,δ-unsaturated alkene skeleton, which is an excellent 1,6-Michael acceptor and shows high reactivity toward soft stabilized nucleophiles. Compared to the many reports on nucleophilic 1,6-addition of 1 , the selective radical 1,6-addition is difficult and rarely reported, with the exception of p -methylene benzoquinones . This is due to the competing side reactions, such as 1,4-radical additions and free radical polymerization.…”
mentioning
confidence: 89%
“…Adamo and co-workers developed 3-methyl-4-nitro-5-alkenyl-isoxazole 1 , bearing a γ,δ-unsaturated alkene skeleton, which is an excellent 1,6-Michael acceptor and shows high reactivity toward soft stabilized nucleophiles. Compared to the many reports on nucleophilic 1,6-addition of 1 , the selective radical 1,6-addition is difficult and rarely reported, with the exception of p -methylene benzoquinones . This is due to the competing side reactions, such as 1,4-radical additions and free radical polymerization.…”
mentioning
confidence: 89%
“…They employed the Cinchona-derived phase-transfer catalyst 20 for the conjugate addition of nitromethane to 17. The key material 17 was based on their brand α,β-unsaturated acid acceptor surrogates derived from 3,5-dimethyl-4-nitroisoxazole 16 [54]. Phase-transfer catalysis imparted good enantioselectivity in the Michael addition (72% ee); further recrystallisation was able to yield enantiopure 18 (>99% ee), with an impact on the yield.…”
Section: Scheme 3 Organocatalytic Desymmetrization Of Glutaric Anhydr...mentioning
confidence: 99%
“… 14 Most significantly, our previous studies demonstrated the existence of profound analogies between the reactivity of heteroaromatic vinylogous nitromethanes, such as 6 , and carbonyl species such as methylketones 1 ( Figure 1 ). 15 …”
mentioning
confidence: 99%